KEBIJAKAN PENETAPAN HARGA PASAR DALAM TEORI MEKANISME PASAR ISLAM - Milat, Muhammad Sihabul; Binti Mutafarida; Yuliani Yuliani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Market economic transactions operate based on price mechanisms, ensuring that transactions are fair for all participating parties, and prices must also reflect fairness. This research is conducted to draw conclusions and formulate them in written text, serving as a theoretical foundation, a guideline for problem-solving, and for developing hypotheses that need to be tested. Economic equilibrium occurs when supply equals demand. Islam contributes comprehensively to the economy. The main pillars of Islamic economics are the ethical and moral aspects of Islam itself. The equilibrium of market mechanisms and price determination from an Islamic perspective has been explained by Islamic economic scholars.